ANÁLISE MULTITEMPORAL DA VEGETAÇÃO DE MATA CILIAR DOS RIOS AQUIDAUANA E MIRANDA - Catarine Tamburini (2025)
Riparian forests are native forests that develop along riverbanks. They have many environmental functions, including the preservation of water resources, landscape, and biodiversity by facilitating the gene flow of fauna and flora, soil protection against erosion, and contributing to climate balance. They act directly in sediment retention, thus preventing siltation along riverbanks, resulting in the stabilization of the terrain. They also serve as shelter and food sources for terrestrial and aquatic fauna. Through two chapters, this research initially aimed to conduct a bibliometric analysis regarding the NDVI index focused on vegetation analyses in Riparian Forests. By analyzing the content of 23 articles, it was observed high quality in the elaboration of the articles, as well as their contents and results, due to the greater rigor of the journals with better classifications. Temperature is the variable that most influences NDVI values, followed by precipitation, and the dry period proved important for maintaining NDVI levels. Using semivariogram analysis with the addition of texture resources increases the accuracy of vegetation classification. In the second chapter, it was proposed to analyze land cover in the Riparian Forest of the entire stretch of the Aquidauana and Miranda River on a temporal scale (2003, 2013, 2023). Through subdivisions regarding the different courses of the river (upper, middle, lower), the main changes that occurred over this period and the status of the quality and conservation of the Riparian Forest vegetation of the Aquidauana and Miranda River – MS were identified, which was obtained by analyzing the vegetation index (NDVI). There are differences in land cover among the areas along the rivers course, but the most notable fact was the significant reduction of forest areas in the lower course, corresponding to the Miranda Municipality region. However, in this region, the largest areas composed of Native Forests still occur, making it essential to ratify subsidies for effective preservation.